2020
DOI: 10.1016/j.ijso.2020.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative analgesic efficacy of caudal dexamethasone added to bupivacaine vs bupivacaine alone for pediatric elective infra-umbilical surgery at (Tikur Anbesa Specialized Hospital), Ethiopia: Prospective cohort study

Abstract: Background: Caudal block is the most preferred technique of postoperative analgesia in pediatrics, despite its limited duration of action. Many additives are used to improve the efficacy of caudal blocks, such as opioids or α2 agonists. Recently, there has been increased use of caudal dexamethasone as postoperative analgesia. Objective: To assess the efficacy of adding caudal dexamethasone on bupivacaine for postoperative analgesia in pediatric infra-um… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Prosser et al stated that the adding of 2 mg / kg tramadol to caudal bupivacaine resulted in an prolong duration of anesthesia. The tramadol addition did not significantly lengthen the effect of caudal bupivacaine [20][21] . Young age, administration of different concentrations of intravenous inhalations, and the use of different methods of pain assessment and sedation may explain differences in the total dose of analgesia prescribed in different studies.…”
Section: Discussionmentioning
confidence: 72%
“…Prosser et al stated that the adding of 2 mg / kg tramadol to caudal bupivacaine resulted in an prolong duration of anesthesia. The tramadol addition did not significantly lengthen the effect of caudal bupivacaine [20][21] . Young age, administration of different concentrations of intravenous inhalations, and the use of different methods of pain assessment and sedation may explain differences in the total dose of analgesia prescribed in different studies.…”
Section: Discussionmentioning
confidence: 72%
“…Ketamine is a good alternative to be an adjuvant to caudal block in pediatric postoperative pain treatment, but fentanyl, neostigmine, and dexamethasone are being clinically practiced in Ethiopia and other resource-poor areas [ [27] , [28] , [29] ]. In many nations, the rationale for the underuse of ketamine for a caudal block concerns neurotoxicity, dose, and uncertainty associated with the child's age, among other factors.…”
Section: Discussionmentioning
confidence: 99%
“…6 Similarly, other studies have revealed that the administration of dexamethasone in the epidural space effectively prolongs the duration of caudal block. [7][8][9][10] However, in a meta-analysis; IV dexamethasone was recommended over caudal dexamethasone for prolonging the analgesic duration of caudal epidural block as there was a risk of potential neurotoxicity from administering Dexamethasone in the epidural space. 11 On the other hand various other studies have shown intravenous (IV) Dexamethasone to effectively prolong the duration of caudal block.…”
Section: Original Articlementioning
confidence: 99%